2019
DOI: 10.1016/j.nicl.2019.101684
|View full text |Cite
|
Sign up to set email alerts
|

Seizure detection by convolutional neural network-based analysis of scalp electroencephalography plot images

Abstract: We hypothesized that expert epileptologists can detect seizures directly by visually analyzing EEG plot images, unlike automated methods that analyze spectro-temporal features or complex, non-stationary features of EEG signals. If so, seizure detection could benefit from convolutional neural networks because their visual recognition ability is comparable to that of humans. We explored image-based seizure detection by applying convolutional neural networks to long-term EEG that included epileptic seizures. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 46 publications
0
90
0
2
Order By: Relevance
“…Regarding the seizure detection task, many studies have shown that the models trained via traditional machine learning algorithms, 55 60 especially SVM and k-NN, deep learning algorithms 61 65 using specific features in time and/or frequency domain based on scalp EEG, or iEEG recordings can successfully detect seizures with multiple types. In particular, Emami and colleagues have proposed a CNN-based seizure detection model.…”
Section: Examination Of Epileptic Brain Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the seizure detection task, many studies have shown that the models trained via traditional machine learning algorithms, 55 60 especially SVM and k-NN, deep learning algorithms 61 65 using specific features in time and/or frequency domain based on scalp EEG, or iEEG recordings can successfully detect seizures with multiple types. In particular, Emami and colleagues have proposed a CNN-based seizure detection model.…”
Section: Examination Of Epileptic Brain Statesmentioning
confidence: 99%
“…In particular, Emami and colleagues have proposed a CNN-based seizure detection model. 61 The model learned the EEG (scalp EEG) characteristics in seizure state and non-seizure state automatically, without additional manual feature extraction procedures, through the supervised learning framework, and was able to detect seizure onset at an average positive rate of 74% when the entire time series EEG was sequentially input by 1 second (100% for input by 1 minute). They also have demonstrated that performance of seizure detection depends on the similarity of seizure onset pattern between training data and test data, i.e., new data with a different onset pattern that those of trained data could not be detected well.…”
Section: Examination Of Epileptic Brain Statesmentioning
confidence: 99%
“…Die Klassifikationskriterien reichen von einfachen Schwellwertverfahren bis zu komplexen Machine-Learning-Methoden wie Support-Vektor-Maschinen, Random-Forest-Verfahren (Entscheidungsbäume) und künstlichen neuronalen Netzwerken [34,37]. Zuletzt kamen auch Deep-Learning-Algorithmen zur Anwendung [38,39]. Die Algorithmen werden zunächst an einem Trainingsdatensatz trainiert und dann an einem unabhängigen prospektiven Datensatz validiert [30,37].…”
Section: Automatische Anfallsdetektion In Derunclassified
“…A majority voting strategy has been adopted to fuse the decisions of the ensemble of CNNs, reaching an average accuracy of 96.1%. In [27], the authors exploited the attitude of the CNNs to process images, rather than 0-D temporal sequences. For this purpose, the raw EEG multichannels data have been firstly filtered, then segmented using a prefixed time window, and finally converted into a series of EEG-plot images.…”
Section: Introductionmentioning
confidence: 99%